Student’s self-efficacy in the implementation of virtual reality media in mathematics learning - Wafiqoh, Risnina; Apriani, Fitri; Zaliman, Iski; Suwandi, Djatmiko (Pendidikan Matematika UNIMOR, 2025)
The implementation of Merdeka curriculum aims to provide the flexibility for both teachers and students in conducting the learning process. Preliminary research at one of the public secondary high schools in Pangkalpinang showed that students had a strong interest in learning, when the information, communication and technology are involved; however, teachers are likely to use the technology-based media in the classroom. This study was conducted to examine the effectiveness of Virtual Reality based learning media on students’ self-efficacy. This study used a quantitative approach with a quasi-experimental design. A total of 60 students participated in this study, consisting of 30 students in the experimental group and 30 students in the control group. This study was conducted in one of junior high schools in Pangkalpinang. The research results were analysed using n-gain, Kolmogorov-Smirnov normality test, Levene’s homogeneity test, and Mann-Whitney U test. The Kolmogorov-Smirnov test showed the significance value of the control group is 0.008 and the significance value of the control group is 0.002. The results indicate that the data were not normally distributed. Therefore, the Mann-Whitney U test was used, resulting a significance value of 0.000. The value obtained is less than 0.05 (< 0.05), so that the alternative hypothesis was accepted. The study proves that VR based learning media can effectively enhance students’ self-efficacy